2020
DOI: 10.1002/lary.28958
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Gender Differences Among U.S. Otolaryngology Board Members

Abstract: Objectives: To determine the representation of women in leadership positions within otolaryngology societies and to compare their academic rank and research productivity to men. Methods: The leadership positions of all U.S. otolaryngology societies were compiled. The Medicare Physician Compare database was used to obtain gender and medical school graduation year for all otolaryngologists. An online search was used to determine board member's academic faculty rank. The Scopus database was used to determine an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…1 Currently, women are underrepresented as chairs, vice chairs, and program directors in otolaryngology and research productivity is also higher for men. [8][9][10] In our study, no statistical difference was noted in the liklihood that men or women would enter academic practice after laryngology fellowship. Despite this, the fact that a relatively high percentage of female otolaryngology graduates pursues a fellowship in laryngology may signify that laryngology is a portal through which many women can enter into academic practice.…”
Section: Discussioncontrasting
confidence: 64%
“…1 Currently, women are underrepresented as chairs, vice chairs, and program directors in otolaryngology and research productivity is also higher for men. [8][9][10] In our study, no statistical difference was noted in the liklihood that men or women would enter academic practice after laryngology fellowship. Despite this, the fact that a relatively high percentage of female otolaryngology graduates pursues a fellowship in laryngology may signify that laryngology is a portal through which many women can enter into academic practice.…”
Section: Discussioncontrasting
confidence: 64%
“…Our results indicate that women hold 12 out of 117 professor positions and nine out of 115 chair positions. Gender disparity in publication productivity was also seen in a study conducted by Hill et al in 2020 24 . The difference in h‐index could be due to women holding fewer leadership positions in general with further stratification as the ranks progress.…”
Section: Discussionmentioning
confidence: 65%
“…Gender disparity in publication productivity was also seen in a study conducted by Hill et al in 2020. 24 The difference in h-index could be due to women holding fewer leadership positions in general with further stratification as the ranks progress. For example, only 8% of department chairs and chiefs are women while 38% of assistant and associate residency program directors are women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women in ophthalmology may have increased numbers of visible role models and available mentors as studies have shown the percentage of women on journal editoral boards and professional society boards are at least in line with the percentage of women in the field as a whole [12]. There is similar gender parity present in the leadership positions of ENT societies relative to the percentage of practicing female ENT surgeons [13]. The development of robust and active mentorship programs for students and residents may be helping to relieve pipeline issues [14].…”
Section: Plos Onementioning
confidence: 99%